KAJIAN KEAMANAN PANGAN BAKSO DAN CILOK YANG BERDAR DI LINGKUNGAN UNIVERSITAS JEMBER DITINJAU DARI KANDUNGAN BORAKS, FORMALIN DAN TPC - Riska Rian Fauziah (Faculty of Agricultural Technology, University of Jember, 2014)
The aims of this study was to determine the food safety of meatballs and cilok which sold around University of Jember. Ramdom sampling methods was used in this study and the collected sample were 30 samples of meatball and 13 samples of cilok. Borax, formalin and TPC test was carried out in this study. The result shows that 92% of cilok sample and 17% meatball sample were detected containing borax but none detected containing formalin. In term of the sanitation, meatballs and cilok circulating in the University of Jember was still lacking due the total plate count of most sample were out of standart, more than 105cfu/g.Keywords: food safety, meatball, borax, formalin, TPC